1985
DOI: 10.1113/jphysiol.1985.sp015883
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of carbon dioxide and pH on central chemoreceptors in the rat in vitro.

Abstract: SUMMARY1. The brain stem, cervical cord and attached phrenic nerve were excised from neonatal rats and superfused in vitro. Respiratory activity was recorded from the phrenic nerve following transaction of all the cranial nerves and dorsal roots.2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 28 publications
(33 reference statements)
4
43
0
Order By: Relevance
“…These rhythmic nervous discharges are consistent with the persistence of respiratory function, since (i) they elicit periodic inspiratory movements of the rib cage (Suzue, 1984), (ii) they originate from central respiratory neurons (Onimaru, Arata & Homma, 1988;Hilaire, Monteau, Gauthier, Rega & Morin, 1990;Smith, Greer, Liu & Feldman, 1990), (iii) they are sensitive to respiratory stimuli such as lung vagal afferents (Murakoshi & Otsuka, 1985) and pH and CO2 levels (Harada, Kuno & Wang, 1985; Monteau, . This preparation has turned out to be a suitable method for pharmacological studies on central respiratory activity, since drugs added to the bathing medium diffuse within the brain stem, act on respiratory (and non-respiratory) neurons, and induce respiratory changes which are not affected by the periphery (Murakoshi, Suzue & Tamai, 1985;Errchidi, Hilaire & Monteau, 1990).…”
Section: Introductionmentioning
confidence: 87%
“…These rhythmic nervous discharges are consistent with the persistence of respiratory function, since (i) they elicit periodic inspiratory movements of the rib cage (Suzue, 1984), (ii) they originate from central respiratory neurons (Onimaru, Arata & Homma, 1988;Hilaire, Monteau, Gauthier, Rega & Morin, 1990;Smith, Greer, Liu & Feldman, 1990), (iii) they are sensitive to respiratory stimuli such as lung vagal afferents (Murakoshi & Otsuka, 1985) and pH and CO2 levels (Harada, Kuno & Wang, 1985; Monteau, . This preparation has turned out to be a suitable method for pharmacological studies on central respiratory activity, since drugs added to the bathing medium diffuse within the brain stem, act on respiratory (and non-respiratory) neurons, and induce respiratory changes which are not affected by the periphery (Murakoshi, Suzue & Tamai, 1985;Errchidi, Hilaire & Monteau, 1990).…”
Section: Introductionmentioning
confidence: 87%
“…The in vitro brainstem-spinal cord preparation from newborn rat is known to respond to hypercapnia mainly by an increase in respiratory frequency (Issa & Remmers, 1992;Okada et al 1993b;Kawai et al 1996); however, it has also been suggested that the amplitude of phrenic nerve activity could increase independently in response to hypercapnia (Harada et al 1985). In the awake adult rat preparation, hypercapnia increases both respiratory frequency and tidal volume .…”
mentioning
confidence: 99%
“…An increase in respiratory burst frequency after basilar artery perfusion or bath superfusion of an acidic Krebs solution is also observed in the isolated newborn brainstem preparation (Harada et al 1985;Tarasiuk & Grossman, 1991;Issa & Remmers, 1992 (Murakoshi, Suzue & Tamai, 1985;Greer, Smith & Feldman, 1991;Di Pascale, Morin, Monteau & Hilaire, 1992) (Neubauer et al 1991) but exists to a large degree in glia and in the endothelium of blood vessels (Pan, Nauss, Bernard, Douglas & Trouth, 1991), confirming the extra neuronal space for the chemotransduction mechanisms. The classical view is that the chemosensitive stimulus is the hydrogen ion (Loeschke, 1982).…”
Section: Discussionmentioning
confidence: 96%
“…Recent evidence, however, indicates that C02 plays an independent role. Using the isolated brainstem preparation of the newborn rat, Harada, Kuno & Wang (1985) …”
mentioning
confidence: 99%